A Study of the Cultural Diplomacy of the Islamic Republic of Iran in International Film Festivals - Ali Rahimi; Fatemeh Azizabadi Farahani; Mahmoud Azizi Soldoz (Religion & Communication)
Holding film festivals that are held every year with a specific title and theme around the world provide special opportunities for participants from host and guest countries. In this global event, opportunities are provided for those involved in film production and a part of professional and amateur audiences to watch, analyze and award awards. In this article, these opportunities are presented as opportunities and threats and strengths and weaknesses. Face to face, the cinema of the Islamic Republic of Iran has been studied in international film festivals, which are part of cultural diplomacy, and has analyzed each of them in terms of the situation they create. Therefore, in order to receive opportunities and threats and strengths and weaknesses created in these festivals by Delphi method and interviews with experts in this field, a questionnaire was prepared and after two stages of answering and collecting and calculating Cronbach's alpha coefficient above 7 out of 123 people and analyzing it. Using the SWOT method, it was possible to identify the mentioned cases, which showed that festivals face 8 opportunities and 8 threats, and also Iranian cinema has 16 strengths and 15 weaknesses. Continue to study more and identify these points and their impact on use and interest. Taking advantage of these situations, several operational proposals were made. These proposals have been analyzed in light of the cultural diplomacy of Iranian cinema and the background of Islamic culture and what is being done today.